Evaluation of Haematological and Immunological Status in Type 2 Diabetics - A. Sohna Chandra Packiavathy; M. Ramalingam (E-Journal of Chemistry)
Type 2 diabetes is a heterogeneous disorder involving impairment of both insulin secretion and insulin action. The immunological and haematological statuses during normal and diseased conditions have been studied. The study groups consisted of 220 patients (110 males, 110 females) and 220 age and sex matched control subjects (110 males, 110 females). The values of IgG, IgM, IgE and IgA were found to be significantly increased. Leucocyte count and erythrocyte sedimentation rate were also found to be increased in the type 2 diabetics as compared to controls. The study suggests that variation in the levels of immunoglobulins and cell count may be involved in the pathogenesis of type 2 diabetes mellitus.